Chemical Retraction Agents – in vivo and in vitro Studies into their Physico-Chemical Properties, Biocompatibility with Gingival Margin Tissues and Compatibility with Elastomer Impression Materials - Nowakowska, Danuta; Saczko, Jolanta; Kulbacka, Julita; Wicckiewicz, Wlodzimierz (Mini Reviews in Medicinal Chemistry, 2017)
Gingival margin retraction/displacement (GMR/D) is a commonly accepted procedure in restorative dentistry. Of the various retraction methods, the chemo-mechanical approach with retraction media and chemical retraction agents (ChRAs) is mostly used. Different local and/or systemic side effects were observed after “chemical attacks” from these retraction agents. Moreover, no consensus exists as to the compatibility of chemical agents with different impression materials. This paper reports the findings of in vivo and in vitro studies and we discuss the physico-chemical properties of chemical retraction agents, their undesirable clinical side effects, biological activity and compatibility with selected groups of elastomer impression materials.
Keywords: compatibility